2020
DOI: 10.1681/asn.2020040509
|View full text |Cite
|
Sign up to set email alerts
|

AKI in Hospitalized Patients with and without COVID-19: A Comparison Study

Abstract: BackgroundReports from centers treating patients with coronavirus disease 2019 (COVID-19) have noted that such patients frequently develop AKI. However, there have been no direct comparisons of AKI in hospitalized patients with and without COVID-19 that would reveal whether there are aspects of AKI risk, course, and outcomes unique to this infection.MethodsIn a retrospective observational study, we evaluated AKI incidence, risk factors, and outcomes for 3345 adults with COVID-19 and 1265 without COVID-19 who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
367
5
25

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(436 citation statements)
references
References 48 publications
39
367
5
25
Order By: Relevance
“…1,7 Previous studies have been limited by small sample size; incomplete follow-up; or have not focused primarily on survival or kidney outcomes. [24][25][26] Our current study of almost 10000 hospitalized patients with COVID-19 with 99%…”
Section: Discussionmentioning
confidence: 91%
“…1,7 Previous studies have been limited by small sample size; incomplete follow-up; or have not focused primarily on survival or kidney outcomes. [24][25][26] Our current study of almost 10000 hospitalized patients with COVID-19 with 99%…”
Section: Discussionmentioning
confidence: 91%
“…Recently published studies on COVID-19 worldwide reported AKI rates in hospitalized patients of 17.9-72.7% in Italy 29,30 , 9.2-18.3% in Korea 31,32 , 19.7-69.2% in Spain 33,34 , 5.8-56.9% in USA 35,36 , 52.2-74.6% in Germany 37,38 , and 4.7-64.1% in France and Belgium 39,40 , which are much higher than the rates in China. The difference may be explained by the fact that only very sick COVID-19 patients were admitted to hospitals in those countries compared to the admission of less sick patients in China.…”
Section: Epidemiology Of Covid-19-associated Acute Kidney Injurymentioning
confidence: 99%
“…Severe COVID-19 was associated with multiple organ injuries such as ARDS [25][26][27] and AKI [28][29][30] , which were identi ed as independent risk factors for mortality in patients with COVID-19. However, the association of ACE-I or ARB use with AKI or ARDS is still not fully understood.…”
Section: Discussionmentioning
confidence: 99%